Adverse Selection, Heterogeneous Beliefs, and Evolutionary Learning - Clemens Buchen; Alberto Palermo (Dynamic Games and Applications, 2021)
We relax the common assumption of homogeneous beliefs in principal-agent relationships with adverse selection. Principals are competitors in the product market and write contracts also on the base of an expected aggregate. The model is a version of a cobweb model. In an evolutionary learning set-up, which is imitative, principals can have different beliefs about the distribution of agents' types in the population. The resulting nonlinear dynamic system is studied. Convergence to a uniform belief depends on the relative size of the bias in beliefs.
Keywords: C61; C73; D82; D83; E32; 330; Evolutionary game theory; Imitation equilibrium; Heterogeneous beliefs; Adverse selection; Cobweb model